2014
DOI: 10.1039/c4cc03946g
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of iron hydrogenase active sites into a highly stable metal–organic framework for photocatalytic hydrogen generation

Abstract: A new biomimetic heterogeneous photocatalyst ([FeFe]@ZrPF) has been synthesized through the incorporation of homogeneous complex 1 [(í-SCH2)2NC(O)C5H4N]-[Fe2(CO)6] into the highly robust zirconium-porphyrin based metal-organic framework (ZrPF). The immobilized biomimetic [Fe2S2] catalyst inside the MOF shows great improvement in hydrogen generation compared to the reference homogeneous catalyst complex 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 40 publications
2
124
0
2
Order By: Relevance
“…Besides other UiO-66/UiO-66-NH 2 [55,[145][146][147][148][149][150] and MIL-101/ MIL-101-NH 2 [151,152] associated work, the photocatalytic performances of MOF-supported catalysts, including UiO-type MOFs, [153][154][155] MOF-5, [56] MIL-125-NH 2 , [156,157] MIL-53-NH 2 , [158] Zr-porphyrin-based MOF (ZrPF), [159] and NU-1000 [160] are also summarized in Table 3. Besides other UiO-66/UiO-66-NH 2 [55,[145][146][147][148][149][150] and MIL-101/ MIL-101-NH 2 [151,152] associated work, the photocatalytic performances of MOF-supported catalysts, including UiO-type MOFs, [153][154][155] MOF-5, [56] MIL-125-NH 2 , [156,157] MIL-53-NH 2 , [158] Zr-porphyrin-based MOF (ZrPF), [159] and NU-1000 [160] are also summarized in Table 3.…”
Section: Mofs As Supportsmentioning
confidence: 99%
“…Besides other UiO-66/UiO-66-NH 2 [55,[145][146][147][148][149][150] and MIL-101/ MIL-101-NH 2 [151,152] associated work, the photocatalytic performances of MOF-supported catalysts, including UiO-type MOFs, [153][154][155] MOF-5, [56] MIL-125-NH 2 , [156,157] MIL-53-NH 2 , [158] Zr-porphyrin-based MOF (ZrPF), [159] and NU-1000 [160] are also summarized in Table 3. Besides other UiO-66/UiO-66-NH 2 [55,[145][146][147][148][149][150] and MIL-101/ MIL-101-NH 2 [151,152] associated work, the photocatalytic performances of MOF-supported catalysts, including UiO-type MOFs, [153][154][155] MOF-5, [56] MIL-125-NH 2 , [156,157] MIL-53-NH 2 , [158] Zr-porphyrin-based MOF (ZrPF), [159] and NU-1000 [160] are also summarized in Table 3.…”
Section: Mofs As Supportsmentioning
confidence: 99%
“…Despite catalytically limiting conditions, namely; recombination of excited states pertaining to [Ru(bpy) 2 (bpy) À ] + and oxidised ascorbate, as well as impeded diffusion of the sensitiser; the activity of the MOF was still roughly three times better than that of the homogeneous adduct. 102 The [FeFe]@ZrPF MOF was assembled by room temperature diffusion of the mimic into the MOF over 48 hours, after which time the distinctive fluorescence emission of the porphyrin moieties was quenched. Accordingly, the authors theorise disproportionation of singly reduced active sites (X 1À ), which go on to form catalytically active doubly reduced species (X 2À ).…”
Section: Mof Supported Water Reductionmentioning
confidence: 99%
“…However, the reaction stopped after a very short reaction time (< 2hours) due to catalyst deactivation. [47][48] Finally, it is interesting to note that while molecular cobaloximes are good catalysts as well, they also suffer, within comparable photochemical conditions, from low stability, with full inactivation after a few hours. [49][50] We also found that the cobaloxime precursor of PCoP was active using the ACN/TEOA system and Ru(bpy) 3 Cl 2 as the photosensitizer under the conditions used with PCoP (SI).As the amount of Co was comparable to that provided by the PCoP catalyst, the data show that the free cobaloxime was slightly less efficient.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%